Studies on Production of a Tempeh-like Meat Analogue from Soybean(Glycine max),Bambara Groundnut(Vgna Subterranae and Lima Bean(Phaseolus lunatus). - Adanlwo, Oladipo Olawale (Obafemi Awolowo University., 2023)
xvi,158 Pages